Vacteens.org: A Mobile Web app to Improve HPV Vaccine Uptake - Woodall, W. Gill; Zimet, Gregory; Kong, Alberta; Buller, David; Reither, Jeannyfer; Chilton, Lance; Myers, Valerie; Starling, Randall (Frontiers in Digital Health, 2021)
U.S. HPV vaccine uptake remains below the Healthy People 2030 goal of 80% series completion. Parental concerns and misinformation about the efficacy and safety of the Human Papillomavirus (HPV) vaccine remain, and may be addressed by digital interventions tailored to their concerns. Reported here are results from a small scale randomized trial testing a mobile web app for parents and their adolescent daughters (ages 11-14 years) encouraging HPV vaccination in New Mexico, an ethnically-diverse U.S. state. Methods. A clinic-cluster randomized trial where pediatric clinics (n=9) were recruited and randomized, and parent-adolescent pairs (n=82) within clinics received either the Vacteens.org/Vacunadolescente.org mobile web app or Usual and Customary (UC) HPV Vaccination information. Parents completed online surveys at baseline and 3-months. Daughters’ HPV vaccine data were collected from the New Mexico State Immunization Information System one year post baseline. Results. Three month survey results found Vacteens.org/Vacunadolescente.org parents to have higher positive HPV vaccine beliefs, iInformed dDecision mMaking, iIntent to vVaccinate and vVaccine cConfidence outcomes than UC parents. HPV vaccine data found higher first dose HPV vaccination (Pearson χ2=6.13, p=.013, Vacteens.org/Vacunadolescente.org group 59.4%, UC group 40.6%), and higher HPV vaccination series completion (Pearson χ2=6.49, p=.011, Vacteens.org/Vacunadolescente.org group 68.4%, UC group 31.6%). Conclusions. The small trial results showed the Vacteens.org/Vacunadolescente.org web app prompted positive vaccine-related attitudes and beliefs, and more HPV vaccination initiation and series completion. Mobile web apps can make decision-making tools for HPV vaccination widely available on digital platforms, reducing vaccine hesitancy and confusion and increase HPV vaccine uptake.